Synthesis, docking studies, in vitro cytotoxicity evaluation and DNA damage mechanism of new tyrosine-based tripeptides - GÖRGÜLÜ, AHMET ORHAN (My University, 2023)
Peptides are one of the leading groups of compounds that have been the subject of a great deal of biological research and still continue to attract researchers\" attention. In this study, a series of tripeptides based on tyrosine amino acids were synthesized by the triazine method. The cytotoxicity properties of all compounds against human cancer cell lines (MCF-7), ovarian (A2780), prostate (PC-3), and colon cancer cell lines (Caco-2) were determined by the 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide assay method, and % cell viability and logIC50 values of the compounds were calculated. Significant decreases in cell viability were observed in all cells (p < 0.05). The comet assay method was used to understand that the compounds that showed a significant decrease in cell viability had this effect through DNA damage. Most of the compounds exhibited cytotoxicity by DNA damage mechanism. Besides, their interactions between investigated molecule groups with PDB ID: 3VHE, 3C0R, 2ZCL, and 2HQ6 target proteins corresponding to cancer cell lines, respectively, were investigated by docking studies. Finally, molecules with high biological activity against biological receptors were determined by ADME analysis.
Keywords: Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Bilimler; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Natural Sciences; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Yaşam Bilimleri (LIFE); TOKSİKOLOJİ; Farmakoloji ve Toksikoloji; BIOCHEMISTRY & MOLECULAR BIOLOGY; MOLECULAR BIOLOGY & GENETICS; Life Sciences (LIFE); TOXICOLOGY; PHARMACOLOGY & TOXICOLOGY; Toksikoloji; İlaç Keşfi; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Sağlık, Toksikoloji ve Mutajenez; Yapısal Biyoloji; Moleküler Biyoloji; Klinik Biyokimya; Kanser Araştırmaları; Biyokimya; Yaşlanma; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Genel Biyokimya, Genetik ve Moleküler Biyoloji; Fizik Bilimleri; Toxicology; Drug Discovery; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Health, Toxicology and Mutagenesis; Structural Biology; Molecular Biology; Clinical Biochemistry; Cancer Research; Biochemistry; Aging; Biochemistry, Genetics and Molecular Biology (miscellaneous); General Biochemistry, Genetics and Molecular Biology; Physical Sciences; ADME; cytotoxicity; DNA damage; molecular docking; peptides